2015
DOI: 10.1002/pssr.201510227
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the scintillation properties of Gd3 Ga3 Al2 O12 :Ce,B single crystals having tailored defect structure

Abstract: A novel approach is reported to minimize various defect centers in Ce doped Gd3Ga3Al2O12 single crystals to improve the scintillation properties. The crystals of Gd3Ga3Al2O12 codoped with 0.2 at% Ce and B (GGAG:Ce,B) have been grown in air and argon ambient using the Czochralski technique. The scintillation light output of crystals grown in Ar ambient was significantly increased after annealing the crystals in air. The measured light output of 60000 ph/MeV for annealed crystals is the highest value reported am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…Scintillation properties of undoped YAG were barely explored in detail due to low light yield and slow luminescence decay. Meanwhile, Ce‐doped garnets did not attract much attention until the development of extremely efficient Al/Ga‐substituted multi component garnets with the light yields of up to 58 000 phot MeV −1 . This value is near the theoretical limit considering the energy gap of these materials .…”
Section: Introductionmentioning
confidence: 99%
“…Scintillation properties of undoped YAG were barely explored in detail due to low light yield and slow luminescence decay. Meanwhile, Ce‐doped garnets did not attract much attention until the development of extremely efficient Al/Ga‐substituted multi component garnets with the light yields of up to 58 000 phot MeV −1 . This value is near the theoretical limit considering the energy gap of these materials .…”
Section: Introductionmentioning
confidence: 99%
“…The nanopowder synthesized by the coprecipitation method has been sintered at 1000 °C for 24 h and the solid-state sintered powder is sintered at 1400 °C for 24 h. The peaks are indexed and matched with the JCPDS-44-0448 database. All the samples show formation of the pure phase of GGAG:Ce. , No peaks corresponding to constituent oxides were observed. The peak width of powder prepared by coprecipitation is broader than powder synthesized by the solid state which indicated that the grain size is smaller in the case of GGAG:Ce powder synthesized by chemical technique.…”
Section: Resultsmentioning
confidence: 89%
“…More details of crystal growth have been given in ref. [30]. A 5× 5× 2 mm 3 crystal was cut from an ingot crystal, polished optically and subsequently coupled to the APD and SiPM for thermal neutron detection.…”
Section: Methodsmentioning
confidence: 99%